2006
DOI: 10.1074/jbc.m510357200
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Effect of Rosiglitazone Is Mediated via Peroxisome Proliferator-activated Receptor γ-activated Maxi-K Channel Opening in Human Umbilical Vein Endothelial Cells

Abstract: Recent evidence shows that peroxisome proliferator-activated receptor ␥ (PPAR␥) ligands induce the antiangiogenic effect in endothelial cells and tumors. In the present study, we elucidated the involvement of maxi-K channel activation in the antiangiogenic effect of rosiglitazone, a well known PPAR␥ ligand in human umbilical vein endothelial cells. We found that the antiangiogenic effects of rosiglitazone were reversed by either bisphenol A diaglycidyl ether, a PPAR␥ antagonist, or iberiotoxin, a maxi-K channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…50 -52 The mechanisms involve the suppression of VEGF receptors and urokinase plasminogen activator expression, induction of PAI-1, and elevation of apoptosis and NO production. 50,52 All these data have clearly demonstrated the importance of PPAR-␥ in regulating endothelial biology (Figure 1). …”
Section: Ppar-␥ Activation/inactivation In Vascular Ecsmentioning
confidence: 99%
“…50 -52 The mechanisms involve the suppression of VEGF receptors and urokinase plasminogen activator expression, induction of PAI-1, and elevation of apoptosis and NO production. 50,52 All these data have clearly demonstrated the importance of PPAR-␥ in regulating endothelial biology (Figure 1). …”
Section: Ppar-␥ Activation/inactivation In Vascular Ecsmentioning
confidence: 99%
“…Recent studies have suggested that prolonged exposure to thiazolidinediones directly improves NO bioavailability in endothelial cells and increases phosphorylation of eNOS at Ser-1177 (12)(13)(14)(15). Phosphorylation of eNOS at Ser-1177 stimulates NO synthesis, and several protein kinases have been demonstrated to phosphorylate eNOS Ser-1177 in endothelial cells, including protein kinase B (also known as Akt) and AMP-activated protein kinase (AMPK) (16 -20), but the protein kinase and signaling mechanism responsible for phosphorylation of eNOS in response to thiazolidinediones is as yet undetermined.…”
mentioning
confidence: 99%
“…NO can directly activate BK Ca [22] and can also be dependent on the nitric oxide-cyclic guanosine monophosphate-dependent protein kinase signal amplification system [23]. The regulation of endothelial BK Ca channel by NO is less clear [24].…”
Section: Discussionmentioning
confidence: 99%